Binospec: A Wide-field Imaging Spectrograph for the MMT. (3rd June 2019) - Fabricant, Daniel; Fata, Robert; Epps, Harland; Gauron, Thomas; Mueller, Mark; Zajac, Joseph; Amato, Stephen; Barberis, Jack; Bergner, Henry; Brennan, Patricia; Brown, Warren; Chilingarian, Igor; et al.
Abstract: Binospec is a high-throughput, 370 to 1000 nm, imaging spectrograph that addresses two adjacent 8′ by 15′ fields of view. Binospec was commissioned in late 2017 at the f/5 focus of the 6.5 m MMT and is now available to all MMT observers. Aperture masks cut from stainless steel with a laser cutter are used to define the entrance apertures that range from 15′ long slits to hundreds of 2″ slitlets. System throughputs, including the MMT's mirrors and the f/5 wide-field corrector peak at ∼30%. Three reflection gratings, duplicated for the two beams, provide resolutions ( λ /Δ λ ) between 1300 and >5000 with a 1″ wide slit. Two through-the-mask guiders are used for target acquisition, mask alignment, guiding, and precision offsets. A full-time Shack-Hartmann wavefront sensor allows continuous adjustment of primary mirror support forces, telescope collimation and focus. Active flexure control maintains spectrograph alignment and focus under varying gravity and thermal conditions.